Fatty acid metabolism driven mitochondrial bioenergetics promotes advanced developmental phenotypes in human induced pluripotent stem cell derived cardiomyocytes - Ramachandra, Chrishan J. A. (2020)
Background: Preferential utilization of fatty acids for ATP production represents an advanced metabolic phenotype in developing cardiomyocytes. We investigated whether this phenotype could be attained in human induced pluripotent stem cell derived cardiomyocytes (hiPSC-CMs) and assessed its influence on mitochondrial morphology, bioenergetics, respiratory capacity and ultra-structural architecture. Methods and results: Whole-cell proteome analysis of day 14 and day 30-CMs maintained in glucose media revealed a positive influence of extended culture on mitochondria-related processes that primed the day 30-CMs for fatty acid metabolism. Supplementing the day 30-CMs with palmitate/oleate (fatty acids) significantly enhanced mitochondrial remodeling, oxygen consumption rates and ATP production. Metabolomic analysis upon fatty acid supplementation revealed a β-oxidation fueled ATP elevation that coincided with presence of junctional complexes, intercalated discs, t-tubule-like structures and adult isoform of cardiac troponin T. In contrast, glucose-maintained day 30-CMs continued to harbor underdeveloped ultra-structural architecture and more subdued bioenergetics, constrained by suboptimal mitochondria development. Conclusion: The advanced metabolic phenotype of preferential fatty acid utilization was attained in hiPSC-CMs, whereby fatty acid driven β-oxidation sustained cardiac bioenergetics and respiratory capacity resulting in ultra-structural and functional characteristics similar to those of developmentally advanced cardiomyocytes. Better understanding of mitochondrial bioenergetics and ultra-structural adaptation associated with fatty acid metabolism has important implications in the study of cardiac physiology that are associated with late-onset mitochondrial and metabolic adaptations.